Studies on Gd doped ZnO nanocrystalline thin films. (January 2015) - Shanthi, S.; Muthukumarasamy, N.; Agilan, S.; Balasundaraprabhu, R.
<x content-type="archive" xml:space="preserve">Abstract</x> Nanocrystalline Gd doped ZnO thin films have been synthesised using pulsed spray pyrolysis method. The structural studies reveal that the Gd doped ZnO films exhibit wurtzite structure and the doped Gd ions occupy Zn sites, and the lattice parameter c axis value was found to decrease with doping. The grain size of the film was calculated using Scherrer's formula and was found to lie in the range of 8·46–10·58 nm. The optical absorbance and transmittance spectra were recorded by using an ultraviolet–visible spectrophotometer in the wavelength range of 200–1600 nm. The band gap value was observed to be in the range of 2·89–3·08 eV.